مقارنة حمولات الرياح والزلازل لنماذج من المداخن البيتونية المسلحة الصناعية المحلية - زكائي طريفي; أيمن حسن (Tishreen University, 2018)
Reinforced  concrete chimneys  are used  to expel gases and exhaust from industrial processes to be differentiated in the upper layers of the atmosphere of high altitudes , to reduce air pollution . They can be conical , cylindrical , or mixed-section (conical - cylindrical) . It has been in the research study of the forces resulting from wind , earthquakes for three models of chimneys . conical , cylindrical, and Mixed-section chimneys , with equal heights of 110 m , As it exists in the Syrian coast . The seismic forces was calculated using the equivalent static method , Wind loads were calculated in both longitudinal and transverse directions . modeling was done using SAP2000.V14 software , have also been drawing shear force , bending moment and  displacement diagrams to the three models . It was concluded that the effect of wind on the three models is greater than the effect  of earthquakes (within the local data) , and the largest earthquake forces were on the conical chimney . While the forces of the wind was the biggest on the cylindrical chimney. And the forces of earthquakes and winds are at least on mixed-section chimney. At the end of the research , it is recommended to use chimneys with a mixed section (conical - cylindrical) in the design of chimneys where the forces on them were the least. تستخدم المداخن البيتونية المسلحة لطرح الغازات والعوادم الناتجة عن العمليات الصناعية إلى ارتفاعات عالية لتفريقها في طبقات الجو العليا, للتخفيف من التلوث الهوائي . ويمكن أن تكون بشكل جذع مخروط  أو اسطوانية أو بمقطع مختلط (مخروطي - اسطواني) . تم في البحث دراسة القوى الناتجة عن الرياح والزلازل لثلاثة  نماذج من المداخن , مخروطية واسطوانية ومدخنة بمقطع مختلط , وذات ارتفاعات متساوية 110 m  . وذلك باعتبارها موجودة في الساحل السوري . تم حساب حمولة الزلازل بالطريقة الاستاتيكية المكافئة كما تم حساب حمولة الرياح بالاتجاهين الطولي والعرضي . تمت النمذجة  باستخدام برنامج SAP2000.V14  , كما تم رسم مخططات العزوم والقص والانتقال للمداخن الثلاث . تم التوصل إلى أن تأثير الرياح على النماذج الثلاث هو أكبر من تأثير الزلازل (ضمن المعطيات المحلية ) , وقوى الزلازل الأكبر كانت على المدخنة المخروطية . بينما قوى الرياح كانت الأكبر على المدخنة الأسطوانية . وقوى الزلازل والرياح هي الأقل على المدخنة بمقطع مختلط . وفي نهاية البحث ينصح باعتماد مداخن بمقطع مختلط ( مخروطي - اسطواني ) في تصميم المداخن حيث القوى عليها كانت الأقل .